Perancangan Sistem Ujian Online Berbasis Web (Studi Kasus di SMP Negeri 1 Cikarang Selatan, Bekasi) - Aditya W Utama (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
The entrance examination is a limited way to measure one's abilities. Examination is intended to measure the knowledge of a person or student. He growing age of increasingly sophisticated technology or teaching methods is done one of them by means of this web-based online exam, with online examinations we do not need to pay extra to buy paper and spend ink to print. The growing age of increasingly sophisticated technology or teaching methods one of which is done by using this web-based online exam, with online exams we don't need to pay extra to buy paper and spend ink to print. Seeing the conditions above, the author intends to conduct research aimed at providing solutions through the assessment of various theories and observations in the field in order to design a web-based online examination system. The application development methodology that I use is the SDLC method (System Develop Life Cycle) with the waterfall process model until the testing phase. The programming language used is PHP by using MySQL as the database. The result of the research is the creation of an application that can speed up the daily exam process by up to 50% of the original time.